Influences of tantalum pentoxide and surface coarsening on surface roughness, hydrophilicity, surface energy, protein adsorption and cell responses to PEEK based biocomposite - Mei, Shiqi; Yang, Lili; Pan, Yongkang; Wang, Deqiang; Wang, Xuehong; Tang, Tingting; Wei, Jie (Colloids and surfaces, B, Biointerfaces, 2019)
[Display omitted] •Tantalum pentoxide (Ta2O5)/polyetheretherketone composite (PTC) was fabricated.•Ta2O5 enhanced thermal, mechanical and surface properties of PTC.•Surface coarsening further improved surface properties of PTC.•BMSCs responses to PTC were significantly promoted by Ta2O5 and surface coarsening. Polyetheretherketone (PEEK) biomaterial has become increasingly popular in orthopedic applications due to its favorable biocompatibility, biostability, mechanical strength and elastic modulus similar to natural bones. In this research, in order to improve the biological performances of PEEK, tantalum pentoxide (Ta2O5) was incorporated into PEEK to fabricate PEEK/Ta2O5 composites (PTC) using a method of cold press-sintering, and surface coarsening of PTC was prepared by sand blasting. The results showed that the Ta2O5 particles were uniformly disperse into PEEK, and thermal and mechanical properties of PTC were enhanced with the increase of Ta2O5 content. In addition, incorporating Ta2O5 into PEEK and surface coarsening could improve surface roughness, hydrophilicity, surface energy and protein absorption of PTC. Furthermore, the adhesion and proliferation as well as osteogenic differentiation of BMSCs on PTC were significantly promoted and regulated by Ta2O5 content and surface coarsening. The results indicated that surface coarsening of PTC (PTCS) with high surface roughness, hydrophilicity and surface energy could induce positive cellular responses, showing good cytocompatibility. PTCS might have a great potential as implants for bone repair.